Realita Pembahasan dalam RUU Pertembakauan - Prayitno, Edik (Oratio Directa (Prodi Ilmu Komunikasi), 2024)
Indonesia is known as one of the best tobacco producing countries in the world. Related to controlling tobacco products so that it benefits the community, there needs to be a clear arrangement from downstream to upstream. To find out whether the legal basis, efforts to protect health, social life, cultural customs and industrial interests. One of the obligations of the Government as a State is to ensure the legal basis governed by clear laws. As a democratic country, Indonesia divides power into three (trias politica); Executive, Legislative and Judiciary.Bearing in mind that there is always interaction between the executive and the legislature in every process of discussion, decision making and the ratification of a law. This is interesting because several laws are of concern to the wider community, due to the lengthy process. Being in the public spotlight, controversial policies, multiplier effects and minutes of meeting minutes that can be accessed by researchers, the groupthink theory in the Tobacco Draft Law is possible to be studied as dynamics in the decision making process from the perspective of communication science.Groupthink theory is defined as a method of consideration used by group members when their desire for agreement exceeds their motivation to assess all existing action plans.The qualitative method is based on the constructivism paradigm which holds that knowledge is not only the result of experience of facts, but also the result of the construction of the thought of the subject under study. Human recognition of social reality is centered on the subject and not on the object, this means that science is not the result of experience alone, but is also the result of construction by thought.Each member of the special committee is a party representative, they express their views according to the party's vision-mission and ideology. However, every policy has the opportunity to become a political commodity, so that the bill which is supposed to be urgent, becomes slow and never ends, because of the tug-of-war.Keywords: Tobacco Bill, Communication process, Groupthink